The Effect of Current Ratio (Cr), Earning Per Share (Eps), Debt to Equity Ratio (Der) And Price to Book Value (Pbv) on Stock Prices in Transportation and Logistics Sector on The Indonesian Stock Exchange 2019-2021 - Kasmawati Kasmawati; Abshor Marantika; Wulan Oktaviani; Irfan Tanjung; Rani Munika; Maya Lastari (Greenation International Journal of Economics and Accounting, 2023)
The research was conducted with the aim to examine the effect of CR, EPS, DER and PBV on stock prices in transportation and logistics sector companies listed on the Indonesian stock exchange 2019-2021. The population in this study are all companies in the transportation and logistics sector listed on the Indonesian stock exchange. Sampling was done by purposive sampling method and 14 companies were selected. Hypothesis testing is done by using multiple linear regression models using SPSS 25.00. Based on the simultaneous test results, the variables CR, EPR, DER and PBV proved to have a significant effect on stock prices. Where partially the CR and EPS variables have no effect on stock prices. The close relationship that occurs between the variables CR, EPS, DER and PBV on stock prices is quite strong with a correlation coefficient (R) og 57.1 percent. White the contribution of the independent variable to the dependent variable is 25.3 percent, the remaining 74.7 percent is explained by other variables that are not included in this research model.